1994
DOI: 10.1007/bf00206957
|View full text |Cite
|
Sign up to set email alerts
|

Expression and chromosomal mapping of the gene encoding the human histone H1.1

Abstract: The expression of a human histone H1 isoform (H1.1) was studied in several human tissues. Northern blot analysis has revealed that this gene is expressed in testis and thymus, but not in other human tissues. In this report, we demonstrate that the expression of the histone H1.1 gene in human testis is restricted to early round spermatids that belong to the fraction of postmeiotic sperm cells. Transcripts hybridizing with the human H1.1 gene could not be detected in testis of mouse, rat, bull or boar. Southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In contrast to the murine H1.1 gene, transcription of the human H1.1 gene occurs post-meiotically (Burfeind et al, 1994). Expression of the DNA replication-dependant H1.1 histone gene in nondividing post-meiotic cells is highly surprising.…”
Section: The Histone H1 Familymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the murine H1.1 gene, transcription of the human H1.1 gene occurs post-meiotically (Burfeind et al, 1994). Expression of the DNA replication-dependant H1.1 histone gene in nondividing post-meiotic cells is highly surprising.…”
Section: The Histone H1 Familymentioning
confidence: 99%
“…Expression of the DNA replication-dependant H1.1 histone gene in nondividing post-meiotic cells is highly surprising. Based on the differences in expression patterns and primary structures, Burfeind et al (1994) concluded that rodent and human H1.1 gene products are not functional homologues.…”
Section: The Histone H1 Familymentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic probe cos5, specific for the 6p21.3 region, was obtained from Dr. D. Doenecke (Göttingen, Germany) and contains a large portion of the histone H1.1 gene sequence (Burfeind et al 1994). The genomic probe cCI6-84, specific for the 6p12 region, was obtained from the Japanese Cancer Research Resources Bank via Dr. K. Hashimoto (Tokyo, Japan) and contains a 40-kb insert including 8 kb of the heat-sensitive protein 90 beta (hsp90 beta) gene sequence (Takahashi et al 1994).…”
Section: Probesmentioning
confidence: 99%
“…To characterize the amplified region further, FISH analysis was also performed with a cosmid probe mapping to the 6p21.3 region and containing a large portion of the histone H1.1 gene (Burfeind et al 1994). As shown in Fig.…”
Section: Cgh Analysis Of A431 Tumour Cellsmentioning
confidence: 99%